Rancang Bangun Alat Pengering Cabai Skala Laboratorium Dengan Pemanfaatan Concentrated Solar Power - Dwi Rahmalina; Agri Suwandi; Diki Handika Edi; Reinnaldy Martonggo (Fakultas Teknik Universitas Pancasila, 2022)
Increasing plantation productivity in Indonesia is currently increasing from year to year, one of the most needed plantation products in the community is red chili, post-harvest handling that is not paid attention to causes chilies to rot quickly. One of the post-harvest handlings of excessive chili so as not to decay is by drying. The tool design and manufacturing method used is the Pahl & Beitz design method and the manufacturing process used includes cutting, bending, perforating, joining and finishing stages. The results of the dryer design carried out are by developing a rack type dryer design or tray dryer, using three shelves as a place or container to dry chili using a radiator system and a fan as a heating device for the drying room. The results showed that the laboratory scale red chili dryer manufacturing process took 374 minutes with a total cost of Rp.4.715.400. As for the red chili drying process carried out for 360 minutes at a temperature of 60C with a weight of 500 grams per shelf, the average moisture content was 40% and the drying rate was 0.55 gram/minute.